Dynamic modeling of organic rankine cycle and its experimental verification - Altun, Ertuğrul. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Renewable energy technologies and waste heat recovery systems have become more important all around the world because of global warming, global climate change, and countries' tendency to decrease fossil fuel consumption. Organic Rankine Cycle is one of the most popular research topics on waste heat recovery systems. In this thesis, a dynamic model of a lab scale Organic Rankine Cycle (ORC) is developed. The main objective of this thesis is to create a dynamic model for ORC system at Bogazici University Renewable Energy Technologies (BURET) laboratory including heat loses and pressure losses in pipes and to validate the model by comparing the simulation results with experiments done at BURET laboratory. The cycle parameters such as temperature and pressure are calculated transiently in the dynamic model. The model is obtained using Modelica language and Dymola program which is an object-oriented modeling software. After the dynamic model testers for each cycle component are created, component models' simulation results are verified by using experimental data taken from ORC setup at BURET laboratory. Once the component models are verified, whole dynamic ORC model is created. Experimental studies are conducted using the ORC setup at BURET laboratory and the results are compared to those of the dynamic model built in this study. It is found that temperature and pressure values for each component's inlet and outlet are accurately simulated by the dynamic model created in this study.
Keywords: Renewable natural resources.; Organic rankine cycle.; Waste heat recovery.